The Concept of State Owned Corporation Subsidiary Governance Incompatible With The Core Business - Rahmadi Tektona; Edi Wahjuni (International Journal of Social Service and Research (IJSSR), 2023)
Company management based on Good Corporate Governance (GCG) principles is an effort to make GCG a rule and guideline for company managers in carrying out their business activities. Corporate governance is also an essential element of driving performance; many studies have proven that corporate governance affects the company’s performance. Implementing the principles of GCG in the management of the company is very important because it guides the company to make decisions appropriately and responsibly and the management of the company to be healthier, thereby increasing the company’s value. This study aimed to analyze corporate governance in Subsidiaries State owned subsidiaries that are incompatible with the core business by using normative juridical research methods, with the data source being secondary data obtained by library research. In secondary data used primary legal material in the form of statutory regulations, secondary legal material in the form of literature related to this research. Based on the research results, the concept of governance of Subsidiaries State owned subsidiaries that do not suit the core business, in general, has not been going well due to the establishment of a subsidiary to pursue profit. If the Good Corporate Governance mechanism does not function properly in the company, this can reduce the company’s value and lead to poor company performance and even loss. If the principles of Good Corporate Governance are appropriately implemented in subsidiaries that do not suit the core business.